Energy consumption minimization in bioethanol dehydration with supercritical fluids - Paulo, Cecilia Inés (2009)
In this work, we propose a rigorous model for bioethanol dehydration process with supercritical propane to minimize energy consumption. Thermodynamic predictions are performed with an upgraded Group Contribution with Association Equation of State, GCA-EOS. As compared to the basic scheme for dehydration with supercritical fluids, vapor recompression, as well as feed preconcentration could be highly energy efficient. We further consider alternative integration schemes between process streams, associated to different nonlinear programming problems. Special attention has been devoted to a new scheme that integrates the vapor recompression scheme to the preconcentration step, which provides additional reduction in total energy consumption. We demonstrate that bioethanol dehydration can be a sustainable alternative that is energetically competitive with molecular sieves in the production of this biofuel. © 2009 Elsevier B.V. All rights reserved.